PENGARUH PEMBERIAN ONGGOK FERMENTASI TERHADAP KONDISI SALURAN PENCERNAAN ITIK PEKING FASE FINISHER UMUR 90 HARI: THE INFLUENCE OF THE ONGGOK FERMENTATION ON THE CONDITION OF THE DIGESTIVE TRACT OF DUCKS PEKINGESE FINISHER AGED 90 DAYS - Inggita, Azzahra Astrid; Wulandari, Eudia Christina; Purwadi, Purwadi (Universitas Boyolali, 2025)
The study aims to determine the interaction between the provision of different fermented cassava pulp in the ration on the pH of the digestive tract. The materials used in the study were 100 DOD of Peking ducks. The materials used were concentrated from New Hope Indonesia, fine cassava pulp, tempeh yeast (Rhizopus sp), and water. The experimental design used was a Completely Randomized Design (CRD) using 3 treatments and 6 replications. Proximate Test Results of fermented cassava pulp: Water 72.00%, Ash 0.40%, LK 1.39%, SK 3.20% and PK 1.02%. The parameters observed were esophageal pH, crop pH, proventriculus pH, ventriculus pH, duodenal pH, jejunum pH, ileum pH, large intestine pH, and cecum pH. The research data were processed statistically with analysis of variance and if there was a significant effect (P<0.05) between treatments, Duncan's Test was carried out at the 5% level. The results showed that the provision of fermented cassava at different levels in the ration did not have a significant interaction (P>0.05) on the pH of the digestive tract. The study concluded that the provision of level T0 contained 19.1% crude protein, T1 contained 19.151% crude protein and T2 contained 19.202% crude protein. So T2 contains the highest crude protein between T0 and T1.